(untitled) (Revista Contexto & Educação, 2026)
We investigated the formation of training experiences that express the problematization of teaching by teachers who teach Science, in continued in-service training, inspired by the Biographical Project Workshops. To this end, we opted for training research, based on the (auto)biographical method, which explores life stories, involving four teachers. To interpret the results, we used Discursive Textual Analysis. The results point to the search, by these teachers, for continued training in the face of dissatisfaction with their teaching practice. Therefore, they arrive at the course wanting to learn a “recipe package” to better teach their students. However, they are surprised by experiences that led them to problematize their teaching practices, awakening them to more reflective and inquisitive processes for/of yourself, personally and professionally, leading them to investigate their own practices and recognize limitations in their actions. Which makes them think about trying new things in their teaching activities. The aspects raised in the problematization can constitute a state of mind, so that teachers are not subject to ready-made “recipes” and are not satisfied with answers that assume unique truths and constantly question themselves about “what” and “how” they do in their teaching, assuming it as an object of permanent investigation and (re)doing.